PENGARUH AUDIT RISK (INHERENT RISK, CONTROL RISK, dan DETECTION RISK) TERHADAP PENENTUAN AUDIT FEE (Studi Empiris pada Kantor Akuntan Publik di Wilayah Malang, Surabaya, dan Jakarta) - Purnamasari, Desy; kin, Nasi (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this research is  to examine the effect of audit risk(inherent risk, control risk, and detection risk) to audit fees. Respondens  in thisresearch were auditors who work in public accounting firms in Malang,Surabaya, and Jakarta. Based on purposive sampling method, the total sample inthis  research was 104 respondents from public    accounting firms in Malang, Surabaya, and Jakarta. Hypothesis in this research used multiple regression analysis.The results of this research indicate that inherent risk and control risk partially doesn’t have  significant effect on determining audit fees, and detection risk partially doesn’t have  significant effect on determining audit fees. But inherent risk, control risk, and detection risksimultaneously show positive and significant effect on determining audit fees